(Un)Encounters of memory: A brief commentary to the symposium 'The discovery of Brasil years later: Social memory and representations of Portuguese and Brazilians' - Sobral, José Manuel (2004)
The concept of social memory is briefly analysed in this paper, especially the contributions given by sociology and anthropology to this concept. It is sustained that social memory can be understood as an ideology or a representation, as a product of a processes of construction of the past, on which state power is fundamental. The survey presented on Vala's and Saint-Maurice paper is also commented, namely in what concerns the role of characterisations of the national character (Brazilian) in the answers to particular questions. Finally, a brief glance is drawn to the Portuguese images about overseas expansion and its implications.  DOI: http://dx.doi.org/10.17575/rpsicol.v17i2.458